Feedback regulation of small RNA processing by the cleavage product. Issue 8 (3rd August 2019) - Durica-Mitic, Svetlana; Görke, Boris
ABSTRACT: Many bacterial small RNAs (sRNAs) are processed resulting in variants with roles potentially distinct from the primary sRNAs. In Enterobacteriaceae sRNA GlmZ activates expression of glmS by base-pairing when the levels of glucosamine-6-phosphate (GlcN6P) are low. GlmS synthesizes GlcN6P, which is required for cell envelope biosynthesis. When dispensable, GlmZ is cleaved by RNase E in the base-pairing sequence. Processing requires protein RapZ, which binds GlmZ and recruits RNase E by interaction. Cleavage is counteracted by the homologous sRNA GlmY, which accumulates upon GlcN6P scarcity and sequesters RapZ. Here, we report a novel role for a processed sRNA. We observed that processing of GlmZ is never complete in vivo . Even upon RapZ overproduction, a fraction of GlmZ remains full-length, while the 5ʹ cleavage product (GlmZ*) accumulates. GlmZ* retains all elements required for RapZ binding. Accordingly, GlmZ* can displace full-length GlmZ from RapZ and counteract processing in vitro . To mimic GlmZ* in vivo, sRNA chimeras were employed consisting of foreign 3ʹ ends including a terminator fused to the 3ʹ end of GlmZ*. In vitro, these chimeras perform indistinguishable from GlmZ*. Expression of the chimeras in vivo inhibited processing of endogenous GlmZ, causing moderate upregulation of GlmS synthesis. Hence, accumulation of GlmZ* prevents complete GlmZ turnover. This mechanism may serve to adjust a robust glmS basal expression level that is buffered against fluctuations in RapZ availability.